VIOLATION OF THE RIGHT TO DEFENSE DURING DETENTION IN THE INVESTIGATORY STAGE OF CRIMINAL PROCEEDING - Forca, Aleksandar (Glasnik Advokatske komore Vojvodine, 2024)
In the paper, the author deals with the subject of a violation of the right to defense during detention in the investigation phase. The main goal of this paper is to differentiate different legal reasoning from established national case law. The paper examines all elements of the right to defense, which relate to the principle of the "right to a fair trial". The first part of the paper provides a basic theoretical understanding of the topic that is the subject of the paper, as a starting point through which differentiation was later performed. The second part of the paper uses normative and comparative legal solutions to domestic and international legal acts, as well as documentary analysis and case studies. During the preparation of the paper, interviews with prominent criminal justice legal experts were conducted to derive opinions of individuals who have a leading role in formulating a widely-accepted case law. Consequently, graphic representations of surveys were used in the paper to adequately present the collected data. The paper concluded that certain understandings of national case law deviate from the current decisions of the International Court of Justice in Strasbourg, as well as the normative decisions of the European Convention for the Protection of Human Rights and Fundamental Freedoms. The main conclusion derived from the present statement is the need for a different practical solution to the violation of the right to defense when ordering detention in the investigation phase